2018
DOI: 10.1007/s00253-018-8960-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the sensing properties of Escherichia coli-based bioreporters for cadmium and mercury

Abstract: Despite the large number of bioreporters developed to date, the ability to detect heavy metal(loid)s with bioreporters has thus far been limited owing to the lack of appropriate genetic systems. We here present a novel approach to modulate the selectivity and sensitivity of microbial whole-cell bioreporters (WCBs) for sensing metal(loid)s via the znt-operon from Escherichia coli, which were applied to quantify the bioavailability of these contaminants in environmental samples. The WCB harboring the fusion gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The limit-of-detection (LOD) of this sensor is about 44.8 ppb for Cd 2+ [25]. Our Work [25] zntA-gfp 44.8 ppb 2-3 h Custom Detection Platform Gireesh et al [24] zntR-zntA(E. coli)-gfp 0.005 ppm 16 h Fluorescence Plate Reader Hurdebise et al [28] zntA-gfp 660 ppb 3 h Flow cytometer Kang et al [29] zntA-gfp 112.4 ppb 2 h Fluorescence microscopy…”
Section: Heavy Metal Testing With the Microfluidic Devicementioning
confidence: 82%
“…The limit-of-detection (LOD) of this sensor is about 44.8 ppb for Cd 2+ [25]. Our Work [25] zntA-gfp 44.8 ppb 2-3 h Custom Detection Platform Gireesh et al [24] zntR-zntA(E. coli)-gfp 0.005 ppm 16 h Fluorescence Plate Reader Hurdebise et al [28] zntA-gfp 660 ppb 3 h Flow cytometer Kang et al [29] zntA-gfp 112.4 ppb 2 h Fluorescence microscopy…”
Section: Heavy Metal Testing With the Microfluidic Devicementioning
confidence: 82%
“…Given that the cadmium response was induced by the ZntR–cadmium ion interaction, it would be possible to modify the metal ion specificity of WCBs by changing the MLBs of ZntR. As reported previously, the specificity of WCBs toward metal ions can be modified by genetic and biochemical engineering [18,19]. However, this approach does not notably increase the variety of target pollutants, because the metal-binding regions of the regulatory proteins involved in other genetic operons, such as ArsR, CueR, NikR, and TetR in arsenic-, copper-, nickel-, and tetracycline-inducible operons, respectively, consist of several amino acids that are not close at the level of primary structure.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the expression of reporter genes in WCBs is determined by the interaction between target materials and regulatory proteins, the target specificity can be modulated by engineering regulatory proteins. In fact, it was shown that the selectivity and sensitivity of WCB based on zinc-responsive operon was modulated by replacing MBLs of ZntR, a regulatory protein in zinc-responsive operon, with different amino acid sequences in our previous reports [17,18,19]. Since amino acid sequences of MBLs of metalloregulators in metal-responsive operons including MerR, ZntR, GolS and ArsR known to interact with Hg, Cd, Au and As, respectively, were identified, it was possible to modulate the selectivity of MBLs by rational design [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the toxic effects of arsenic species, the cells exposed to arsenic species were incubated for 4 h as OD 600 values were measured. The biosensor assays were performed according to the protocol used in our previous study with minor modification [27]. Briefly, the fluorescence intensity from E. coli biosensors induced by arsenic species was measured using FC-2 spectrophotometers upon 1 and 2 h of incubation.…”
Section: Biosensor Assays For Selectivity and Specificitymentioning
confidence: 99%